Enhanced modelling of planar radial-loaded deep groove ball bearings with smooth-contact formulation - Moreno, Raúl Gismeros (2024)
Bearings are mechanical components designed to restrain the relative rotary motion between moving parts and transmit loads with low friction. Their performance directly impacts the durability, efficiency and reliability of various machinery. Bearing failures can lead to serious consequences, including economic costs, repair/stoppage times, accidents and regulatory compliance issues. In the context of Industry 4.0, the development of detailed and reliable computational models for simulating bearings’ dynamics plays a crucial role in establishing digital twins and implementing advanced predictive maintenance strategies. This work focuses on modelling radial-loaded deep groove ball bearings under the multibody systems dynamics framework. The components of the bearing (inner and outer rings, rolling elements, and cage) are treated as separate bodies and different modelling approaches are employed to define the interactions between them. A smooth contact approach is utilized to characterize the contact/impact phenomena, providing flexibility and efficiency in monitoring the whole contact event. In this sense, suitable normal and friction contact force models are used to describe those interactions between the contacting bodies. Subsequently, several multibody models of radial-loaded deep groove ball bearings are developed considering different modelling assumptions, resulting in dynamic analyses with various levels of complexity. The underlying simplifications are described, and their main advantages and shortcomings are discussed. Furthermore, a new complex contact interaction is presented. The simulation results demonstrated the significant impact of accurately selecting the modelling parameters. The promising results of this study pave the way for future investigations, extending to other geometries of rolling contact bearings and working conditions.